Manajemen Masjid Dalam Peningkatan Kualitas Pengurus dan Jamaah Masjid Al-Birr Perumnas Wekke’e Kota Parepare - Muhammad Qadaruddin; Ramli; Nurlaela Yuliasri (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Improving the quality of jama'ah through the management of the mosque, doneby: how to organize the mosque, how to plan, organize, implement and evaluate so thatthe planned program gets input. The stages of planning include the selection of speakers,packaging messages, media selection, to the level of effects of program implementation.Furthermore, the results of the implementation of mosque management activities, it isexpected there is an increase in knowledge management and pilgrims about tajwid andzakat profesi. Most of the board and the pilgrims when asked questions and asked to readthe verses of the Qur'an by the speakers, have been able to mention the letters hijaiyahwell, understand the law if one in reading the Koran, the question and enthusiasm relatedto professional zakat by board and congregation is a testament to the increasingunderstanding of board and congregation. As an output of mosque managementactivities.